APAKAH IKLAN TELEVISI MASIH KUAT MEMPERSUASI KONSUMEN DI ERA TEKNOLOGI, KOMUNIKASI, DAN INFORMASI - Jusuf, Calvin Sinatra; Hermanto, David Rivaldy (LP2M Institut Teknologi dan Bisnis Asia Malang, 2019)
Nowadays, more and more companies continuously conduct product innovation in order to survive the market competition. One of the strategy to survive the competition is by advertising. Advertisement can be done through a lot of platform, for instance: television, radio, newspaper, magazine, and online platform. In this technological era, advertisement through television is still preferable. According to research, advertising through television is one of the most effective platform since spending rate due to tv commercials is increasing every single year. But on the other hand, television could also be not the most effective platform due to high advertising cost, vast segmentation, and unorganized running time. Because of that reason, it should be researched further whether advertising through television is effective or not.